The Effect of Friends Counseling on Social Interaction of Students of Class XI IPA 5 MAN 3 Medan - Abdurrahman Abdurrahman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to determine the effect of peer counseling on the social interaction of students in class XI IPA 5 MAN 3 Medan. This study uses a quasi-experimental method. The sample is 36 students of MAN 3 Medan. Data collection techniques were carried out through the distribution of questionnaires. The data were analyzed using a different test. The results showed that: There is an effect of peer counseling on social interaction of students in class XI IPA 5 MAN 3 Medan with the calculation results obtained by the price tcount ttable = (14.66 > 1.688). Therefore, it can be concluded that peer counseling to improve intrapersonal competence, one of which is the problem of social interaction, is considered feasible to be used as a counseling service that can be modified according to conditions, schools and student problems.